STRATEGI PEMBELAJARAN KETERAMPILAN BERBICARA MELALUI PROGRAM ARABIC CAMP (STUDI KASUS DI PUSDIKLAT UNIDA GONTOR DAN AKBAR.ID) - Ahmad Fauzi; Mohammad Samsul Ulum; Faisol Samsul Ulum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and compare the speaking skill (maharah kalam) learning strategies implemented through the Arabic Camp program at Pusdiklat UNIDA Gontor and Akbar.id. The study is motivated by the importance of speaking skills in Arabic language learning and the need for innovative, communicative, and contextual learning strategies. Arabic Camp, as a form of non-formal learning, is considered effective in creating an intensive language environment that encourages students to actively use Arabic in daily communication. The approach used in this research was qualitative, using a multiple-case study model. Data collection was conducted through field observations, interviews with informants, and analysis of relevant documents. All data obtained was then analyzed descriptively to illustrate the phenomenon under study. The findings reveal that the Arabic Camp program at Akbar.id is based on partner schools’ needs, while at Pusdiklat UNIDA Gontor it originates from academic needs and has developed into an institutional training program. Both institutions apply student-centered learning and communicative approaches with an emphasis on speaking practice. Akbar.id focuses on providing frequent speaking opportunities, whereas Pusdiklat UNIDA Gontor applies a more structured approach through skill integration, stimulus, and scaffolding. In terms of language environment, Akbar.id applies a modeling approach without coercion, while Pusdiklat UNIDA Gontor uses a persuasive and humanistic approach. This study concludes that the Arabic Camp program is effective in improving students’ speaking skills, particularly in terms of confidence and active participation, influenced by learning strategies, tutor roles, and language environment. Keywords: Speaking skill, Arabic Camp, learning strategies, language environment.